2012
DOI: 10.1089/scd.2011.0224
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Properties and a Clinical Relevance of Multipotent Stem Cells Derived from Cord Blood Samples Stored in the Biobanks

Abstract: Several innovative therapies with human umbilical cord blood stem cells (SCs) are currently developing to treat central nervous system (CNS) diseases. It has been shown that cord blood contains multipotent lineage-negative (LinNEG) SCs capable of neuronal differentiation. Clinically useful cord blood samples are stored in different biobanks worldwide, but the content and neurogenic properties of LinNEG cells are unknown. Here we have compared 5 major methods of blood processing: Sepax, Hetastarch, plasma deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Interestingly, the use of this scaffold or these cells alone resulted in no significant reduction in lesion volume (Lu et al ., ). Similar results were observed by our team after intracranial transplantation of MSCs encapsulated in macroporous gelatin‐laminin cryogels (Jurga et al ., , ). These types of implants significantly reduced inflammation, glial scars, and facilitated the migration of neuroblasts into lesion sites (Jurga et al ., , , and Sarnowska, Jurga e t al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the use of this scaffold or these cells alone resulted in no significant reduction in lesion volume (Lu et al ., ). Similar results were observed by our team after intracranial transplantation of MSCs encapsulated in macroporous gelatin‐laminin cryogels (Jurga et al ., , ). These types of implants significantly reduced inflammation, glial scars, and facilitated the migration of neuroblasts into lesion sites (Jurga et al ., , , and Sarnowska, Jurga e t al .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were distributed evenly within the interconnected pores with good cell‐cell interactions. We previously showed that this scaffold's structure, elasticity and biophysical properties were compatible with brain tissue extracellular matrix and that such scaffolds could be promising materials for future regenerative medical applications (Jurga et al ., , ).…”
Section: Research Focusmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, human cord blood cells were reported to contain cells with neurogenic properties [13][14][15]. In order to detect whether there are any neural precursor cells in the CD34+ fraction of CB, we cultured CB CD34+ cells directly on laminin-coated tissue culture plates in ReNcell medium in the presence of human EGF and bFGF, which is a well established and standard culture condition for human neural stem cells (Millipore).…”
Section: Conversion Of Cord Blood Cd34+ Cells Into Neural Stem Cells mentioning
confidence: 99%
“…In addition, hUCB-MSCs have also been extensively studied for neurogenic potentials [105,81,[108][109][110][111]. Recently, Zhang and colleagues [76] used condition mediumconstituted olfactory ensheathing cells for the differentiation of mesenchymal stem cells into neuronal cells.…”
Section: Human Umbilical Cord Blood Stem Cells Easily Differentiates mentioning
confidence: 99%